Breakdown of gastric mucus in presence of Helicobacter pylori. Issue 1 (January 1991) - Sidebotham, R L; Batten, J J; Karim, Q N; Spencer, J; Baron, J H
Abstract : The potential of Helicobacter pylori to degrade gastric mucus was examined. Colonies of H pylori cultured from antral mucosal biopsy specimens of patients with non-autoimmune gastritis were washed with sterile saline, passed through a sterilisation filter, and the filtrate examined for urease, protease, and mucolytic activity. The filtrate failed to hydrolyse bovine serum albumin, or to degrade stable mucus glycoprotein structures of high particle weight that had been separated from human gastric mucus on Sepharose 2B. The high particle weight mucus glycoprotein was, however, extensively degraded when incubated with H pylori filtrate (which possessed urease activity) in the presence of 2 M urea, to release fragments of Mr approximately 2 X 10(6). The high particle weight mucus glycoprotein was also broken down to a comparable extent when incubated with Jack bean urease in the presence of 2 M urea, or 1 M ammonium carbonate, or 40 mM carbonate-bicarbonate buffer (pH 8.7), but not when treated with 4 M urea alone, or Jack bean urease alone. These results indicate that the loss of high particle weight mucus glycoprotein in gastric mucus from patients with gastritis and gastric ulcers is unlikely to be due to the mucolytic action of an extra-cellular protease produced by H pylori, but it may result from the destabilising effects of a carbonate-bicarbonate buffer, generated at the mucosal surface when H pylori urease hydrolyses transuded plasma urea.